Effect of Replacement of Protein from Soybean Meal with Protein from Wolffia Meal [Wolffia globosa (L). Wimm.] on Performance and Egg Production in Laying Hens - Chantiratikul, A.; Chinrasri, O.; Chantiratikul, P.; Sangdee, A.; Maneechote, U.; Bunchasak, C. (International Journal of Poultry Science, 2010)
Wolffia meal [Wolffia globosa (L). Wimm.] was examined as a protein replacement for Soybean Meal (SBM) in the diets of laying hens. A total of 180 Rohman laying hens of 71 weeks old of age were randomly allocated into 5 groups; each group contained 4 replicates with 9 hens per replicate according to Completely Randomized Design. The dietary treatments were T1 = control diet; T2, T3, T4 and T5 = 25, 50, 75 and 100% of the CP from SBM was replaced by the CP of Wolffia meal, respectively. The results found the decreased feed intake and ME intake (p